Esgoto doméstico tratado como fonte de água e nutrientes no cultivo sem solo do antúrio (Anthurium andraeanum) - Alves, Thiago Roberto (Universidade Federal de São Carlos, 2023)
The agricultural sector in recent years has shown an increase in demand for water and nutrients, however, human activities have impacted negatively on the availability of these resources in nature, where the natural distribution of water that was already disproportionate on planet Earth, has become more intense. An alternative to mitigate the low availability of water and fertilizers, in a sustainable way, is the application of treated domestic wastewater, which can meet the water demand of plants, besides being a source of nutrients and organic matter. Thus, this study aimed to evaluate the main impacts of the application of treated domestic wastewater in protected cultivation of anthurium (Anthurium andraeanum). The experiment was conducted in suspended benches, where the anthurium plants were grown in coconut fiber inside Styrofoam troughs, in protected cultivation. The three treatments applied were: (TRA) treated domestic effluent supplemented with mineral fertilizers, (TA) drinking water supplemented with mineral fertilizers and (TR) treated domestic effluent only. The experiment was performed in a randomized block design, in which quantitative data were subjected to the Tukey test at 5% and Shapiro-Wilk test to attest the normality of the data. The results collected showed that when applying only the treated domestic wastewater (TR), the plants presented nutritional deficiency and low productivity. The biometric parameters (stem length, spadix, spathe, largest leaf and number of flowers) and productivity resulting from the TRA treatment showed no statistical difference in relation to the TA treatment, proving that by using treated domestic effluent the high productivity was maintained with the economy of 3.5 m3 of drinking water and 21.8% of mineral fertilizers. Even with the detection of the presence of Escherichia coli in the treated domestic effluent, the cultivation was considered safe with the absence of contamination in the plants. Thus, it is concluded that the application of treated domestic wastewater as an alternative and sustainable source of water and fertilizers on coconut fiber substrate in a protected environment was feasible in anthurium cultivation, without compromising the health safety of the professionals involved.
Treated domestic waste as a source of water and nutrients in the soil-free growing of anturio (Anthurium andraeanum)
Keywords: Anthurium andraeanum; Efluente doméstico tratado; Fibra de coco; Fertirrigação; Sumi; Treated household effluent; Coconut fiber; Fertigation; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO